Design and Build an Employee Leave Application System - Muhammad Ridwan Effendi; Januar Saputra (Journal of Information Systems and Management (JISMA), 2022)
The development of science and technology that continues to grow and progress, makes all activities in human life faster and is required to be more efficient in utilizing information technology as a data processing base, in order to be able to follow the flow of information development in the globalization era. Computer technology can be used to support the development of information systems in utilizing information technology in this era of globalization. Likewise, companies that want to develop the quality and performance of each employee by using a data processing support tool, namely a computer. With the computer as a data processing tool, the information needed from various fields within a company can be computerized. Speaking of data processing tools, currently the LP3I Jakarta Polytechnic, Depok Campus, which is engaged in education, still has several shortcomings, especially in terms of services to employees that are data processing, namely filing for employee leave. Due to the operational standards that have been set so far in the HRD section for every employee who will apply for leave still using the manual method first, namely by how each employee who will apply must fill out the form manually first and of course this method is less effective and efficient for every employee who will apply for leave. From the results of the study, it was concluded that the Application for Employee Leave at the LP3I Polytechnic Jakarta, Depok Campus still uses the manual method. The author suggests that institutions can implement a more computerized system in their manual system, in order to make it easier to carry out data processing such as recording leave reports as well as effectiveness and efficiency in the process of applying for leave systematically, so that it can produce useful and useful information